Bioaccessibility and bioactivities of phenolic compounds from microalgae during in vitro digestion and colonic fermentation. Issue 2 (20th December 2022) - Li, Kunning; Duan, Xinyu; Zhou, Linhui; Hill, David R. A.; Martin, Gregory J. O.; Suleria, Hafiz A. R.
Abstract : Conceptual framework of the microalgae in vitro digestion and colonic fermentation. Abstract : Microalgae are a developing novel source of carbohydrates, phenolic compounds, carotenoids and proteins. In this study, in vitro digestion and colonic fermentation were conducted to examine the total phenolic content and potential antioxidant activity of four microalgal species ( Chlorella sp., Spirulina sp., Dunaliella sp., and Isochrysis sp.). The bioaccessibility of targeted phenolic compounds and the short-chain fatty acid (SCFA) production were also estimated. Particularly, Spirulina sp. exhibited the highest total phenolic content (TPC) and free radical scavenging (2, 2′-diphenyl-1-picrylhydrazyl, DPPH) capacity after gastrointestinal digestion of 7.93 mg gallic acid equivalents (GAE) per g and 2.35 mg Trolox equivalents (TE) per g. Meanwhile, it had the highest total flavonoid content (TFC) of 1.07 quercetin equivalents (QE) per g after 8 h of colonic fermentation. Dunaliella sp. and Isochrysis sp. showed comparable ferric reducing antioxidant power (FRAP) of 4.96 and 4.45 mg QE per g after 4 h of faecal reaction, respectively. p-hydroxybenzoic and caffeic acid almost completely decomposed after the intestine and fermented in the colon with the gut microflora. In Dunaliella sp. and Isochrysis sp., these phenolic acids were found in the colonic fermented residual, probably due to the presence of dietary fibre and the interactions with other components. All four species reached the highest values of SCFA production after 16 h, except Spirulina sp., which displayed the most increased total SCFA production after 8 h of fermentation. It is proposed that Spirulina sp. could be more beneficial to gut health.